Pemanfaatan Limbah Spent Bleaching Earth (SBE) Sebagai Bahan Baku Pembuatan Briket - Siti Aisyah Sukma; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The need for energy is continuously increasing and the availability of fuel is depleting, the necessary to save energy source. Saving can be through the use of fuel or energy sourced from renewable energy. Therefore, it is necessary to conduct research to obtain alternative fuels that can be renewed such as spent bleaching earth (SBE) waste. SBE is solid waste that comes from the bleaching of crude palm oil. The hoped that SBE solid waste can be reused so that SBE waste does not become an environmental problem because it is existence has not been optimally untilized. This research will utilize SBE waste as raw material for making briquettes with the addition of tapioca adhesive. Keywords: Briquettes, Spent Bleaching Earth, Tapioca Adhesive